John Edwin Scarff (1898-1978) and endoscopic choroid plexus coagulation: A historical vignette - Azab, Waleed A. (Medknow Publications & Media Pvt Ltd, 2014)
John Edwin Scarff (1898-1978) was one of the pioneers of neuroendoscopy and the head of the Department of Neurological Surgery at Columbia University in New York from 1947 to 1949. In this article, we highlight the pioneering and longstanding efforts of John E. Scarff in support of endoscopic choroid plexus coagulation. These efforts represent an important part of the rich history of neuroendoscopy and a legacy to which the current procedure owes a great credit.